2022
DOI: 10.4103/jgid.jgid_276_21
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Bacterial Colonization and Urinary Tract Infection after Indwelling of Double-J ureteral Stent and Percutaneous Nephrostomy Tube

Abstract: Introduction: Infections associated with catheter in the upper urinary tract (CUUT), which include the double-J stent and the percutaneous nephrostomy (PCN) tube, get particularly infected in patients with specific risk factors for developing an infection. Methods: A retrospective observational study was carried out by compiling data from the hospital information system of a tertiary care center from 2019 to 2021 to evaluate infections in patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Previous studies have suggested that the pathogens of double-J stent-related infections mainly include Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis and Klebsiella pneumoniae . 12 , 21 , 28 In this study, we found that under the condition of double-J stent associated urinary tract infection, the pathogenic bacteria culture rate of double-J stent was significantly higher than that of urine (67.65% vs 35.29%). In addition, we also found that the main pathogenic bacteria in the urine were Escherichia coli (30.55%) from Gram negative bacteria, while the main pathogenic bacteria in double-J stent were Enterococcus faecalis from Gram positive bacteria (27.53%).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous studies have suggested that the pathogens of double-J stent-related infections mainly include Escherichia coli, Pseudomonas aeruginosa, Enterococcus faecalis and Klebsiella pneumoniae . 12 , 21 , 28 In this study, we found that under the condition of double-J stent associated urinary tract infection, the pathogenic bacteria culture rate of double-J stent was significantly higher than that of urine (67.65% vs 35.29%). In addition, we also found that the main pathogenic bacteria in the urine were Escherichia coli (30.55%) from Gram negative bacteria, while the main pathogenic bacteria in double-J stent were Enterococcus faecalis from Gram positive bacteria (27.53%).…”
Section: Discussionmentioning
confidence: 66%
“…[8][9][10] Previous studies have shown that long-term indwelling of double-J stent is an important risk factor for recurrent urinary tract infection. 21 In addition, the increase of double-J stent retention time significantly increases the risk of gross hematuria, pain, bladder irritation, urinary tract infection and fever. 22 However, there are few reports on the etiology of urinary tract infection caused by long-term (1-3 months) double-J stent indwelling, as well as the characteristics of pathogenic bacteria and drug resistance in urine and double-J stent.…”
Section: Discussionmentioning
confidence: 99%
“…As observed in Table 3, among the 100 MDR microorganisms tested for susceptibility to the antibiotics, the overall susceptibility to Doxycycline was 35% (35/100, 35%), which was significantly higher in comparison to the overall susceptibility of Cefixime (17/100, 17%) which is in contrast to a study conducted by Ramdhani et al [1] where the test isolates were found to demonstrate better susceptibility to Tetracyclines. Tetracycline is a bacteriostatic agent that was found to be more effective in treating the infections caused by the bacterial isolates in our study cohort due to extensive Beta-lactam resistance that has been observed in isolates identified from other infections in studies conducted at our center [26].…”
Section: Discussionmentioning
confidence: 96%